Cuci karpet home delivery system / Mohd Syafiq Ishak - Ishak, Mohd Syafiq (2016)
In business industries, order, service and standard operation client system is widely involved in their daily activities. The name and address is needed to be updated frequently to make the management team to deal with easy. Cuci Karpet Home Delivery System is one of the web based system and that is specially developed for ABS Cuci Karpet. All related information has been gathered from the client. Currently, only sales activity is done using a computerized system and the rest activities are done manually. Some problems have occurred such as data is kept in paper based like receipt which make it exposed to risk of getting lost, wet and dirty. It also may lead to human errors in calculating and lateness of the rest of the activities. Therefore, the computerized system that will develop is for solving the problems occur or might occur and increase the productivity in the services.